Revised diagnosis of the genus Gonorhynchus McClelland (Teleostei: Cyprinidae: Labeonini) with redescription of G. latius (Hamilton) and revalidation of G. wattanah (Sykes) - Ciccotto, Patrick J.; Page, Lawrence M. (Zootaxa, 2016)
A new diagnosis of the genus Gonorhynchus McClelland 1838 from South Asia is proposed. Seven species are contained in the genus: G. latius (Hamilton 1822), G. diplochilus (Heckel 1838), G. wattanah (Sykes 1839), G. macmahoni (Zugmayer 1912), G. burmanicus (Hora 1936), G. bicornis (Wu 1977), and G. periyarensis (Menon & Jacob 1996). Gonorhynchus latius, a senior synonym of the type species G. brevis M’Clelland 1839 is redescribed. Crossocheilus gohama (M’Clelland 1839) and Crossochilus rostratus Günther 1868 are considered junior synonyms of G. latius, and a neotype is designated for G. latius. Gonorhynchus wattanah (Sykes 1839) from the Krishna and Godavari River basins in western India is revalidated and redescribed with the designation of a neotype. Akrokolioplax Zhang & Kottelat 2006 is a junior synonym of Gonorhynchus.